Protein powder derived nitrogen-doped carbon supported atomically dispersed iron sites for selective oxidation of ethylbenzene. Issue 34 (18th August 2021) - Cheng, Yujie; Sun, Qingdi; Huang, Liyun; He, Qian; Zhang, Hao; Wang, Pengbo; Zhang, Ying; Shi, Shaolin; Zhang, Xingcong; Gan, Tao; He, Xiaohui; Ji, Hongbing
Abstract : A single atom catalyst Fe1 /NC, synthesized by ball milling with protein powder as the nitrogen source, exhibited superb performance for selective oxidation of ethylbenzene. Abstract : Atomically dispersed Fe species embedded in the nitrogen-containing carbon supports (Fe1 /NC) are successfully synthesized using a ball milling approach, with commercial protein powder as the nitrogen source. The catalyst exhibits outstanding performance in the oxidation of aromatic compounds containing saturated C–H bonds into corresponding ketones under ambient conditions, which is superior to those of a nanoparticle catalyst (Fe n /NC) and a metal-free catalyst (NC).